2017
DOI: 10.3390/ma10070695
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nanoscale CaO-Al2O3-SiO2-H2O and Na2O-Al2O3-SiO2-H2O Using the Hydrothermal Method and Their Characterization

Abstract: C-A-S-H (CaO-Al2O3-SiO2-H2O) and N-A-S-H (Na2O-Al2O3-SiO2-H2O) have a wide range of chemical compositions and structures and are difficult to separate from alkali-activated materials. Therefore, it is difficult to analyze their microscopic properties directly. This paper reports research on the synthesis of C-A-S-H and N-A-S-H particles with an average particle size smaller than 300 nm by applying the hydrothermal method. The composition and microstructure of the products with different CaO(Na2O)/SiO2 ratios a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…In addition, a broad featureless hump caused by amorphous aluminosilicate was observed between 25 • and 35 • 2θ [4]. As the curing temperature increased to 95 • C, all K-A-S-H products remained amorphous at the 1-day age.…”
Section: X-ray Diffraction Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, a broad featureless hump caused by amorphous aluminosilicate was observed between 25 • and 35 • 2θ [4]. As the curing temperature increased to 95 • C, all K-A-S-H products remained amorphous at the 1-day age.…”
Section: X-ray Diffraction Analysismentioning
confidence: 97%
“…The proportions of nano-SiO 2 , nano-Al 2 O 3 , KOH, and deionized water are shown in Table 1. Nanoscale K-A-S-H gel was synthesized according to our previous hydrothermal method [3,4]. The samples are named as follows: using K-A-S-H1.0 1 -1d-95 as an example, the K-A-S-H1.0 indicates a K 2 O/SiO 2 ratio in the K-A-S-H system of 1.0, the subscript indicates a SiO 2 /Al 2 O 3 ratio of 1, the 1d indicates a curing time of 1 day, and the 95 indicates that the material was cured at a temperature of 95 • C.…”
Section: Synthesis Of K-a-s-hmentioning
confidence: 99%
“…This study used nanoscale C-A-S-H gel synthesized according to the hydrothermal method listed in literature [ 25 ], with a CaO/SiO 2 ratio of 1.0 a SiO 2 /Al 2 O 3 ratio of 2.0, and a water/solid ratio of 8.0. Figure 1 and Figure 2 show the micromorphology and particle size distribution of the synthetic C-A-S-H gel under scanning electron microscope.…”
Section: Methodsmentioning
confidence: 99%
“…By applying the synthesized C-A-S-H gel to AAS, we can investigate the effect of synthetic C-A-S-H gel on the early-stage shrinkage of AAS mortar. In this research, amorphous C-A-S-H gel powder was prepared by hydrothermal method using nano-SiO 2 and nano-Al 2 O 3 as raw materials [ 25 ]; The powders were then added to the AAS mortar via two different methods. The effect of synthesized C-A-S-H gels on the shrinkage of AAS mortar was studied and a series of tests were performed to determine the autogenous shrinkage and drying shrinkage.…”
Section: Introductionmentioning
confidence: 99%
“…The tensile peak at 887 cm −1 was attributed to Si-O-Na [26]. The spectra also showed a Si-OH stretching peak at 970 cm −1 [27,28], and Si-OH and H-O-H stretching vibrational peaks at 1454 cm −1 and 3450 cm −1 , respectively [29][30][31]. The results indicated that NaOH destroyed Si-O-Si bond under calcination, while Si-OH and Si-O-Na were formed at the same time to activate the silicon.…”
Section: Characterization Of Ashmamentioning
confidence: 97%